Employees' perception towards managers leadership characteristics in islamic organizations - Mastuyah, Binti Haji Sahari (Universiti Malaysia Sarawak, 2008)
The purpose of this study is to determine the perception of employees in Islamic organization towards manager leadership characteristics and the factors that influence it. The findings of the study indicates that personality and intelligence ability is the most important variable that influence the employees perception towards managers leadership characteristics followed by coaching, task-related and communication.